Identification of a candidate biomarker from perfusion MRI to anticipate glioblastoma progression after chemoradiation. - Khalifa, J.; Tensaouti, F.; Chaltiel, L.; Lotterie, J.-A.; Catalaa, I.; Sunyach, M.; Ibarrola, D.; Noël, G.; Truc, G.; Walker, P.; Magné, N.; Charissoux, M.; et al. (European Radiology, 2016)
Objective: To identify relevant relative cerebral blood volume biomarkers from T2* dynamic-susceptibility contrast magnetic resonance imaging to anticipate glioblastoma progression after chemoradiation.Methods: Twenty-five patients from a prospective study with glioblastoma, primarily treated by chemoradiation, were included. According to the last follow-up MRI confirmed status, patients were divided into: relapse group (n = 13) and control group (n = 12). The time of last MR acquisition was tend; MR acquisitions performed at tend-2M, tend-4M and tend-6M (respectively 2, 4 and 6 months before tend) were analyzed to extract relevant variations among eleven perfusion biomarkers (B). These variations were assessed through R(B), as the absolute value of the ratio between ∆B from tend-4M to tend-2M and ∆B from tend-6M to tend-4M. The optimal cut-off for R(B) was determined using receiver-operating-characteristic curve analysis.Results: The fraction of hypoperfused tumor volume (F_hPg) was a relevant biomarker. A ratio R(F_hPg) ≥ 0.61 would have been able to anticipate relapse at the next follow-up with a sensitivity/specificity/accuracy of 92.3 %/63.6 %/79.2 %. High R(F_hPg) (≥0.61) was associated with more relapse at tend compared to low R(F_hPg) (75 % vs 12.5 %, p = 0.008).Conclusion: Iterative analysis of F_hPg from consecutive examinations could provide surrogate markers to predict progression at the next follow-up.Key Points: • Related rCBV biomarkers from DSC were assessed to anticipate GBM progression. • Biomarkers were assessed through their patterns of variation during the follow-up. • The fraction of hypoperfused tumour volume (F_hP g ) seemed to be a relevant biomarker. • An innovative ratio R(F_hP g ) could be an early surrogate marker of relapse. • A significant time gain could be achieved in the management of GBM patients.